Thermal effects of lateral supra‐permafrost water flow around a thermokarst lake on the Qinghai–Tibet Plateau. Issue 13 (24th May 2017) - You, Yanhui; Yu, Qihao; Pan, Xicai; Wang, Xinbin; Guo, Lei; Wu, Qingbai
Abstract: Both the inflow and outflow of supra‐permafrost water to lakes play important roles in the hydrologic process of thermokarst lakes. The accompanying thermal effects on the adjacent permafrost are required for assessing their influences on the development of thermokarst lakes. For these purposes, the lake water level, temperature dynamics, and supra‐permafrost water flow of a lake were monitored on the Qinghai‐Tibet Plateau. In addition, the spatial and temporal variation of the active layer thickness and permafrost distribution around the lake were investigated by combining ground penetrating radar, electrical resistivity tomography, and borehole temperature monitoring. The results revealed that the yearly unfrozen supra‐permafrost water flow around the lake lasted approximately 5 months. The temperature and water level measurements during this period indicate that the lake water was recharged by relatively colder supra‐permafrost water from the north‐western lakeshore and was discharged through the eastern lakeshore. This process, accompanied by heat exchange with the underlying permafrost, might cause a directional difference of the active layer thickness and permafrost characteristics around the lake. Specifically, the active layer thickness variation was minimal, and the ice‐rich permafrost was found adjacent to the lakeshore along the recharge groundwater pathways, whereas a deeper active layer and ice‐poor permafrost were observed close to the lakeshore from which the warm lake water was discharged. This study suggests that the lateral flow of warm lake water can be a major driver for the rapid expansion of thermokarst lakes and provides clues for evaluating the relationships between the thermokarst expansion process and climate warming.